Studying abroad: Exploring factors influencing nursing students' decisions to apply for clinical placements in international settings. (August 2015) - Kent-Wilkinson, Arlene; Dietrich Leurer, Marie; Luimes, Janet; Ferguson, Linda; Murray, Lee
Summary Background For over 15 years the College of Nursing at the University of Saskatchewan has facilitated study abroad clinical placements in a number of countries to enhance student learning. Nursing students often find their study abroad experience to be a defining moment in their educational program, and in their personal and professional growth. Objectives The main objective of this research was to explore factors influencing nursing students' decisions to study abroad. Design A descriptive longitudinal design study was conducted using an online survey. Settings The Study Abroad Survey was distributed to all undergraduate and graduate nursing students, in all years of all programs, at all sites of the College of Nursing, University of Saskatchewan in Saskatchewan, Canada. Participants A total of 1058 nursing students registered in the 2013-2014 academic year were surveyed. Methods The data were collected using an online survey administered by Campus Labs™ (2014). Results Students indicated that their interest in study abroad international experiences was high (84%), with many perceived benefits, but barriers to participation were also high for these students. Financial barriers topped the list (71%), followed by family responsibilities (30%) and job obligations (23%). Conclusion The research highlights the factors behind student decision making related to international placements, and provides the basis for improvements to the College of Nursing's International Study Abroad Program (ISAP). Previous travel and international service learning, resulting in increased perceived value of a study abroad experience may prove to be the more significant factor influencing decision making, rather than financial barrier.